Biomechanics and running economy - Anderson, T. (Sports Medicine, 1996)
Running economy, which has traditionally been measured as the oxygen cost of running at a given velocity, has been accepted as the physiological criterion for 'efficient' performance and has been identified as a critical element of overall distance running performance. There is an intuitive link between running mechanics and energy cost of running, but research to date has not established a clear mechanical profile of an economic runner. It appears that through training, individuals are able to integrate and accommodate their own unique combination of dimensions and mechanical characteristics so that they arrive at a running motion which is most economical for them. Information in the literature suggests that biomechanical factors are likely to contribute to better economy in any runner. A variety of anthropometric dimensions could influence biomechanical effectiveness. These include: average or slightly smaller than average height for men and slightly greater than average height for women; high ponderal index and ectomorphic or ectomesomorphic physique; low percentage body fat; leg morphology which distributes mass closer to the hip joint; narrow pelvis and smaller than average feet. Gait patterns, kinematics and the kinetics of running may also be related to running economy. These factors include: stride length which is freely chosen over considerable running time; low vertical oscillation of body centre of mass; more acute knee angle during swing; less range of motion but greater angular velocity of plantar flexion during toe-off; arm motion of smaller amplitude; low peak ground reaction forces; faster rotation of shoulders in the transverse plane; greater angular excursion of the hips and shoulders about the polar axis in the transverse plane; and effective exploitation of stored elastic energy. Other factors which may improve running economy are: lightweight but well-cushioned shoes; more comprehensive training history; and the running surface of intermediate compliance. At the developmental level, this information might be useful in identifying athletes with favourable characteristics for economical distance running. At higher levels of competition, it is likely that 'natural selection' tends to eliminate athletes who failed to either inherit or develop characteristics which favour economy.